Misperceptions of harm among Natural American Spirit smokers: results from wave 1 of the Population Assessment of Tobacco and Health (PATH) study (2013–2014). Issue Volume 26:Issue e1(2017) (6th December 2016) - Pearson, Jennifer L; Johnson, Amanda; Villanti, Andrea; Glasser, Allison M; Collins, Lauren; Cohn, Amy; Rose, Shyanika W; Niaura, Raymond; Stanton, Cassandra A
Abstract : Introduction: This study estimated differences in cigarette harm perceptions among smokers of the Natural American Spirit (NAS) brand—marketed as 'natural', 'organic' and 'additive-free'—compared to other smokers, and examined correlates of NAS use. Methods: Data were drawn from wave 1 of the Population Assessment of Tobacco and Health (PATH) study, a nationally representative study of US adults (2013–2014). Weighted analyses using a subset of current adult smokers (n=10 565) estimated the prevalence of NAS use (vs all other brands) and examined associations between NAS use and sociodemographics, tobacco/substance use, tobacco harm perceptions, quit intentions, quit attempts and mental/behavioural health. Results: Overall, 2.3% of adult smokers (920 000 people in the USA) reported NAS as their usual brand. Nearly 64% of NAS smokers inaccurately believed that their brand is less harmful than other brands compared to 8.3% of smokers of other brands, after controlling for potential confounders (aOR 22.82). Younger age (18–34 vs 35+; aOR 1.54), frequent thinking about tobacco harms (aOR 1.84), past 30-day alcohol use (aOR 1.57), past 30-day marijuana use (aOR 1.87) and sexual orientation (lesbian, gay, bisexual, 'other' or 'questioning' vs heterosexual; aOR 2.07) were also associated with increased odds of smoking NAS. Conclusions: The majority of NAS smokers inaccurately believes that their cigarettes are less harmful than other brands. Given the brand's rapid growth and its more common use in vulnerable groups (eg, young adults, lesbian, gay, bisexual, 'other' or 'questioning' adults), corrective messaging and enforcement action are necessary to correct harm misperceptions of NAS cigarettes.